A Mixed-integer Programming Approach to Group Control of Elevator Systems with Destination Hall Call Registration - Wu, Y.; Tanaka, S. (2020 IEEE International Conference on Industrial Engineering and Engineering Management (IEEM), 2020)
In this research, we focus on group control of an elevator system with destination hall call registration where passengers can directly register destination floors at every elevator lobby. To improve the elevator performance when transporting passengers, finding the optimal passenger-to-car assignment and car routing is considered as a good way. We formulate the problem of optimizing passenger-to-car assignment and car routing as a mixed-integer programming problem to minimize the average waiting time of all passengers waiting at elevator lobbies. Then, we perform computer simulation using a commercial integer programming solver and examine the effectiveness of the proposed optimization model. A conventional approach which is applied in most current elevator system is also compared with our approach.